Serrated flow behaviors in a Ni-based superalloy - Xiaoyang Zhang; Ruifeng Dong; Yuhong Zhao; Dong Liu; Ling Yang; Hua Hou (Materials Research Express, 2021)
Serrated flow behaviors in Ni-20Cr-18W alloy were studied under different deformation conditions. It was found that there are no serrations observed on the tensile curves of the alloy at the temperature of lower than 250 °C and the strain rate of 10 ^−3 s ^−1 . As the deformation temperature improves, the serrations first starts with the type A (250 °C) and transfers to the mixed type A + B (300 °C and 400 °C), then to the mixed type B + C (500 °C). Meanwhile, the serration behaviors are closely related with the strain rate. It showed that when the deformation temperature is fixed, the serration curves starts with the type A (10 ^−3 s ^−1 ), then transfers to the mixed type A + B (10 ^−2 s ^−1 ) and eventually to type D (10 ^−1 s ^−1 ) with the increasing strain rates from 10 ^−3 s ^−1 to 10 ^−1 s ^−1 . Results showed that the serration behaviors of the alloy are related to the normal PLC effect. Combined with the McCormick’s model, the activation energy for the serrated flow behavior in this alloy is calculated to be 103.386 kJ mol ^−1 and the value of m  +  β to be 2.514, which suggests that the serrated flow of Ni-20Cr-18W superalloy is related to the interplay between the substitutional solute atoms and the movable dislocations.